2011
DOI: 10.1002/acp.1732
|View full text |Cite
|
Sign up to set email alerts
|

Paranormal belief and the conjunction fallacy: Controlling for temporal relatedness and potential surprise differentials in component events

Abstract: Recent research suggests paranormal believers are especially prone to the 'conjunction fallacy'. The current study extends this work by presenting believers and non-believers with eight paranormal plus eight non-paranormal scenarios. Participants were given either a paranormal or virtually identical non-paranormal version of each scenario. Of these, half incorporated component events which were (virtually) co-occurring with half including components which were temporally disjointed. Analysis of Covariance (ANC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
49
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 41 publications
11
49
1
Order By: Relevance
“…These findings complement previous work that has demonstrated that education in probability and statistical inference does reduce gambling fallacies (e.g., & Lindeman, 2005;Blackmore & Troscianko, 1985;Bressan, 2002;Brotherton & French, 2014;Dagnall et al, 2007;Gervais, 2015;Gervais & Norenzayan, 2012;Lindeman & Aarnio, 2007;Musch & Ehrenberg, 2002;Pennycook et al, 2013;Rogers et al, 2009;Rogers et al, 2011).…”
Section: Study Three (Chapter Four)supporting
confidence: 89%
See 1 more Smart Citation
“…These findings complement previous work that has demonstrated that education in probability and statistical inference does reduce gambling fallacies (e.g., & Lindeman, 2005;Blackmore & Troscianko, 1985;Bressan, 2002;Brotherton & French, 2014;Dagnall et al, 2007;Gervais, 2015;Gervais & Norenzayan, 2012;Lindeman & Aarnio, 2007;Musch & Ehrenberg, 2002;Pennycook et al, 2013;Rogers et al, 2009;Rogers et al, 2011).…”
Section: Study Three (Chapter Four)supporting
confidence: 89%
“…There exists a substantial body of evidence that supports the contention that lower probabilistic reasoning ability also facilitates paranormal belief susceptibility (Blackmore & Troscianko, 1985;Bressan, 2002;Brotherton & French, 2014;Dagnall, Parker, & Munley, 2007;Musch & Ehrenberg, 2002;Pennycook, Cheyne, Koehler, & Fugelsang, 2013;Rogers, Davis, & Fisk, 2009;Rogers, Fisk, & Wiltshire, 2011). Additional cognitive-based individual susceptibility factors have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Various complementary lines of research are consistent with the general idea that irrational beliefs are related to a tendency to misperceive patterns in randomness. For instance, conspiracy beliefs are correlated with constructs such as paranormal beliefs (Barron, Morgan, Towell, Altemeyer, & Swami, ; Darwin, Neave, & Holmes, ; Lobato, Mendoza, Sims, & Chin, ; Newheiser et al, ; Swami et al, ), the tendency to attribute agency and intentionality where it does not exist (Douglas, Sutton, Callan, Dawtry, & Harvey, ; Imhoff & Bruder, ), and the conjunction fallacy (Brotherton & French, ; for illustrations of the relationship of the conjunction fallacy with paranormal belief, see Rogers, Davis, & Fisk, ; Rogers, Fisk, & Wiltshire, ). Although these studies indicate links between conspiracy theories and a variety of heuristics and cognitive biases, and are therefore suggestive of a link between pattern perception and conspiracy belief, direct evidence is currently lacking.…”
Section: Illusory Pattern Perception and Irrational Beliefsmentioning
confidence: 99%
“…Thus, without the need to actually work out the probabilities, experience allows us, through a process of associative learning and perhaps without conscious awareness, to focus on the less likely event in the conjunctive case and the more likely in the disjunctive since these have the much greater impact on the respective joint probability outcomes. Over the years we have accumulated evidence consistent with this possibility (Fisk, ; Fisk & Pidgeon, ; Rogers, Fisk & Wiltshire, ) as have other researchers (e.g., Kariyazono, ; Lu, ; Thuring & Jungermann, ; Wyer, ). However, we have yet to consider conjunctive and disjunctive judgments containing the same component events.…”
Section: Introductionmentioning
confidence: 59%
“…We have focused on the relationship between the actual estimated component probabilities and the conjunctive probability estimate demonstrating that that for the most part, for conjunctive judgments only the less likely component has a direct influence on the outcome while for disjunctive judgments, this role is performed by the more likely component. In each case, for most judgments, the other component appears to play no direct role (Fisk, ; Fisk & Pidgeon, ; Rogers, Fisk & Wiltshire, ). Clearly our own results are difficult to reconcile with much of the existing literature.…”
Section: Introductionmentioning
confidence: 99%